2014
DOI: 10.1111/psyp.12192
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potential N270 delayed and enhanced by the conjunction of relevant and irrelevant perceptual mismatch

Abstract: Event-Related Potential (ERP) studies using delayed match-to-sample tasks have demonstrated the presence of two components, N270 and N400, possibly reflecting the sequential processing of multiple sources of endogenous mismatch. To date, studies have only investigated secondary sources of mismatch between a single cue and target. In this study, we used distractor stimuli to investigate the effect of a secondary source of mismatch distinct from the task relevant stimulus. Subjects performed such a task in two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
5
19
0
Order By: Relevance
“…The identification of both N270 and N400 components was also within expectations because our participants were required to do more complex conflict processing due to multiple sources of semantic violations (Bennett et al, 2014;Wang et al, 2003). The wide scalp distribution of the violation-evoked N270s in our study was also a finding that is well aligned with the previous literature (Wang et al, 2003).…”
Section: Erp Results: Violationsupporting
confidence: 89%
“…The identification of both N270 and N400 components was also within expectations because our participants were required to do more complex conflict processing due to multiple sources of semantic violations (Bennett et al, 2014;Wang et al, 2003). The wide scalp distribution of the violation-evoked N270s in our study was also a finding that is well aligned with the previous literature (Wang et al, 2003).…”
Section: Erp Results: Violationsupporting
confidence: 89%
“…Consistent with prior findings, frontal N2 was found to be more negative in the less attractive condition, while LPP was enlarged in response to more attractive faces (Ma et al, ; Werheid, Schacht, & Sommer, ; Zhang et al, ). N2 is well suggested to reflect cognitive conflict (Bennett, Duke, & Fuggetta, ). In this study, male participants always hoped to observe attractive faces and when less attractive ones were presented, a more negative N2 was elicited.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that mismatches in task-relevant and task-irrelevant dimensions are processed automatically and independently. In another study, Bennett et al [2] found that the presentation of a visual distractor enhanced the N270 amplitude both in a perceptual match and mismatch conditions compared to situations with no distractor. They concluded that the distractors may differentially affect the N270 through the generation of task-irrelevant mismatch responses.…”
Section: Introductionmentioning
confidence: 93%